HILAH AL-SYARI’AH SEBAGAI UPAYA DALAM MENGUJUDKAN MAQASHID SYAR’IAH - Dr. Elimartati M.Ag (JURIS (Jurnal Ilmiah Syariah), 2017)
Hilal refers to special actions which are taken as the efforts in changing Islamic laws. This is done by prioritizing physical deeds of the available law by means of particular methods to arrive at desired goals. This can only be performed by those who have specific skills and cannot be detected physically. Hilal can be regarded as one of alternate solutions to make things easier as long as no intention to legalize the forbidden ones and to forbid the legal ones, no violence toward the principles of Islamic law and merely the good sake of society.